Computation offloading and resource management scheme in mobile edge computing - Qiuping LI; Junhui ZHAO; Yi GONG (Dianxin kexue)
Mobile edge computing (MEC) is an innovative computing paradigm.Offloading computing tasks to MEC server can effectively solve the contradiction between resource-constrained of mobile user and computing-intensive applications.Moreover,it can meet the delay of computing task and reduce energy consumption of mobile user.The current research results and achievements of computation offloading scheme in MEC system were summarized and the existing problems and challenges were analyzed.Furthermore,the development directions of MEC in the future were explored.